Republic of Uganda Agriculture Sector Public Expenditure Review - World Bank (World Bank, Kampala, 2019)
The government of Uganda (GoU) regards agriculture as a key economic sector to support Uganda’s vision 2040 and the transition to middle-income status. It recognizes that public spending on agriculture has a pivotal role in equipping the sector to fulfil its potential to drive economic growth, create employment for a rapidly growing and predominantly young population, and ultimately reduce poverty. To improve the quality and effectiveness of public expenditures in agriculture, Uganda has conducted its second agriculture public expenditure review (AgPER) since 2010. Overall, the performance in implementing policy recommendations from the 2010 AgPER has been mixed. This summary presents the key messages emerging from the review and recommends policy and strategic actions for improving the efficiency and effectiveness of spending on agriculture in Uganda.